Asset liability management model: The case of selected Islamic banks in Malaysia / Chong Hui Ling - Chong , Hui Ling (2017)
There have been questions recently about the ability of the Islamic bank as the main competitor of the conventional bank in preventing future banking crisis from recurring. If they are to fulfil this objective, Islamic banks must have robust treasury management mechanisms in place, since effective treasury functions like asset and liability management are crucial to avoiding the risks of insolvency and bank collapse. This study proposes an approach using a multi-objective penalty cost function, which allows the management of assets and liabilities of a bank in a realistic environment that has been simulated and proven to enhance the performance of the system. Specifically, this research has been conducted with the core objective to develop a customised programming model for multi-purpose optimisation using this penalty cost method that ties together divergent objectives unique to Islamic banks. This method produces a solution that minimises the gap between these objectives, targets and actual performance. The study takes Bank Islam Malaysia Berhad‟s (BIMB) financial data to validate the model. The multi-faceted objectives consist of the bank‟s expected returns and risks tolerance with constraints (also known as restraining functions to reflect the limitations placed on the Islamic bank‟s operating requirements), established using computational mathematics and algorithms with the aid of the MATLAB programming software. The research innovates by adding the wealth objectives of the three Islamic shareholding classes: musharakah partnership, mudaraba investment, and shareholder capital. Five years‟ financial data from 2009 to 2013 were sampled from secondary sources like Thompson Reuters‟ DataStream, the bank‟s financial statements, and other sources such as market yields from Islamic Interbank Money Market website. The output from the model is a set of solutions for funds allocation that minimises the asset liability performance gap for BIMB. The study contributes by combining computational tractability with religious oriented asset liability management. This multiple objective (henceforth is used interchangeably with multi-objective) optimisation – something which would have been difficult to implement in the days when information technology was not as advanced as it is today, is implemented in this study. The multi-objectives are subject to both binding and non-binding constraints to reflect the actual Islamic banking environment. The second outcome of this research is BIMB‟s optimal portfolio as a benchmark model for the academic industry for future contributions to the body of knowledge in this field. Algorithms established for the optimisation processes are documented for the study. Interviews with treasury committees of BIMB bank and feedback from the MATLAB system were taken to validate and determine the model‟s efficiency. This research contributes to the growing literature of innovation in asset liability management techniques through computational mathematics and financial modeling. It adds value to the operational and strategic decision makers of Islamic banks. It also provides pointers to future research directions to academicians and researchers from this field.